2020
DOI: 10.2139/ssrn.3523907
|View full text |Cite
|
Sign up to set email alerts
|

Destitution and Paths to Justice

Abstract: Introduction How is destitution defined in law? The legal definition and the JRF definition The state's duty to prevent/relieve destitution A legal perspective on routes into destitution Social security Debt Housing Social security and destitution Legal support for problems of destitution Case studies on destitution and paths to justice Key recommendations 1. A statutory duty on destitution 2. Resourcing legal interventions 3. Access to social security Emerging recommendations on debt and housing Further resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Although some of the participants in receipt of benefits undoubtedly felt degraded by experiences of poverty or their interactions with the social security system, it would be a leap to suggest there was clear evidence of what the UK courts have—to date—been prepared to recognise as inhuman or degrading treatment. Although Adler's () view that this kind of development is far from unthinkable is noted, if not explicitly endorsed, by the Special Rapporteur (Alston, ), case law to date suggests such a conclusion would only be possible following detailed examination of an individual litigant's circumstances (McKeever et al, ).…”
Section: Discussion: Towards a New Understanding Of Dignity In Socialmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some of the participants in receipt of benefits undoubtedly felt degraded by experiences of poverty or their interactions with the social security system, it would be a leap to suggest there was clear evidence of what the UK courts have—to date—been prepared to recognise as inhuman or degrading treatment. Although Adler's () view that this kind of development is far from unthinkable is noted, if not explicitly endorsed, by the Special Rapporteur (Alston, ), case law to date suggests such a conclusion would only be possible following detailed examination of an individual litigant's circumstances (McKeever et al, ).…”
Section: Discussion: Towards a New Understanding Of Dignity In Socialmentioning
confidence: 99%
“…Consequently, it was suggested that a Scottish social security system would place greater emphasis on protection against poverty, a sentiment now reflected in the Act. Aspects of the system implicated as contributors to severe poverty (Fitzpatrick, Bramley, Sosenko, & Blenkinsopp, ; Goulden, ; McKeever, Simpson, & Fitzpatrick, ) were a particular focus for interviewees' ire. One politician stated that “the use of destitution as a deliberate act of government policy is something that I think appals most people,” and the imposition of destitution as a matter of policy through the sanctions regime was among the most frequent complaints.…”
Section: (In)dignity (Dis)respect and (Un)fairness: Devolved Policymentioning
confidence: 99%
“…The destitution research in the UK mirrors this, where individuals experiencing destitution saw benefits as liable to rise, fall or disappear at the whim of a largely unaccountable decision maker (McKeever et al 2018;for Australia, see Human Rights Law Centre et al 2019:13-14;Harmer 2009:25-26).…”
Section: Uk and Australia Comparedmentioning
confidence: 95%
“…It is not unusual for legal and social scientific definitions to differ, and destitution is a case in point. The UK legal definition of destitution is drawn from a range of legislative and jurisprudential sources and, as a result, is a much less coherent concept (McKeever et al ). The most comprehensive statutory definition comes from the Immigration and Asylum Act 1999 (UK, s. 95), which states that destitution consists of the inability to access adequate accommodation and other essential needs, defined through case law.…”
Section: Meeting Basic Needs: Legal Definitions Of Destitution and Hamentioning
confidence: 99%
See 1 more Smart Citation